KARAKTERISTIK PANTUN ACEH - Mohd. Harun (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
The objective of this study is to describe characteristics of Aceh verse. The description covers: (1) number of verses per couplet, (2) long and short verse, (3) content of verse, and (4) poetical nuance of verse. Data of this study were obtained from document of Aceh’s verse and SMS. The study reveals that each couplet of Aceh verse consists of verses that varies from: 2, 3, 4, 6, 8 and 12 verses.  Relying upon its length, Aceh verses may consist of a one-complete sentence verse and some couplets verses or a brief story.  Contents of Aceh verses are classified into: (1) religious verses, (2) advice verses, (3) tradition verses, (4) fate verses, (5) young verses, (6) joke verses, (7) kidding verses, (8) condolences verses, (9) happiness verses, (10) children verses, and (11) seumapa verses.  Based on poetical nuances, a perfect  Aceh’s verse should advice coherent rhymes and rhythms (pakhok and buhu) incorporating intended message, couplets and contents.